EMBODIED DHARMA: EXPLORING THE ROLE OF YOGA IN MODERN HINDU RELIGIOUS LIFE - I Ketut Budi Rach Suarjaya; I Komang Dian Adi Purwadi (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2025)
Yoga, as an embodied spiritual discipline rooted in Hindu philosophical traditions, has undergone significant reinterpretation in the modern era. While contemporary global culture often frames yoga as a wellness practice, its deeper foundations remain intrinsically connected to dharma—ethical living, self-realization, and devotional consciousness. This study explores the role of yoga in shaping modern Hindu religious life by examining its theological meanings, ritual integrations, ethical implications, and emerging digital expressions. Through textual analysis of classical sources such as the Yoga Sūtra, Bhagavad Gītā, and Haṭha Yoga Pradīpikā, combined with observations of contemporary Hindu communities in urban and digital environments, this research highlights the continuity and transformation of yoga as both spiritual embodiment and cultural practice. The findings reveal that yoga continues to function as a vital medium of dharma: harmonizing mind, body, and spirit; reinforcing devotional practices; and enabling Hindus to navigate modern challenges, mental health concerns, and globalized identities. In modern Hindu religiosity, yoga emerges not merely as physical exercise, but as a lived theology—where spiritual insight is cultivated through disciplined embodiment and mindful action in everyday life.